2022
DOI: 10.3390/jcm11102922
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Use for Emotional Dysregulation in Children and Adolescents with ADHD and ADHD and ASD: A Naturalistic Study

Abstract: Emotional dysregulation (ED) is common in attention-deficit/hyperactivity disorder (ADHD). Nonetheless, research on ADHD in children with autism spectrum disorder (ASD) and ADHD is still ongoing. Several studies suggest that methylphenidate (MPH) may be effective for ED in ADHD, while there is not enough evidence about its use in ASD with comorbid ADHD. This naturalistic study aims to investigate the effectiveness of immediate- and extended-release MPH in the treatment of ED in 70 children and adolescents (6–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Also, without reaching significant differences probably due to the small size of this sample, the emotional DP showed a slightly higher score in the comorbid compared with the other clinical groups. Other authors have found that impaired emotional self‐regulation is more prevalent in youth with ADHD or/and autism (Bierens et al, 2023; Ventura et al, 2022) and that the shared association of these characteristics could predict social challenges (Jaisle et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Also, without reaching significant differences probably due to the small size of this sample, the emotional DP showed a slightly higher score in the comorbid compared with the other clinical groups. Other authors have found that impaired emotional self‐regulation is more prevalent in youth with ADHD or/and autism (Bierens et al, 2023; Ventura et al, 2022) and that the shared association of these characteristics could predict social challenges (Jaisle et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sensory dysregulation, pain perception in children and adolescents with ADHD is regulated with chronic MPH application (Wolff et al, 2016). Furthermore, the stimulant lessens anxiety (Snircova et al, 2016;Deslauriers et al, 2019;Jager et al, 2019), and has been shown to decrease emotional dysregulation in children with ADHD (Kutlu et al, 2017;Gamli and Tahiroglu, 2018;Ventura et al, 2022) potentially through reducing impulsivity (Gamli and Tahiroglu, 2018). MPH may lessen anxiety through the reduction of dopaminergic functional connectivity between the amygdala and the rostral anterior cingulate cortex (Berry et al, 2019).…”
Section: Chronic Administration Of Methylphenidatementioning
confidence: 99%
“…These are products of emotional dysregulation (ED). Specifically, an inability to modulate emotional responses, resulting in extreme reactions of an internalizing or externalizing nature that are inappropriate for developmental age (Shaw et al, 2014;van Stralen, 2016;Ventura et al, 2022).…”
Section: Emotional Regulation and Adhdmentioning
confidence: 99%
“…Individual studies suggest that psychostimulant medication reduces emotional lability, irritability and aggressive behavior among children and adolescents with ADHD (e.g., Fernández de la Cruz et al, 2015;Suzer Gamli & Tahiroglu, 2018;Ventura et al, 2022). Nonetheless, not many systematic and meta-analytic reviews exist that examine this on a wider scale, those that do exist point towards methylphenidate 's efficacy (Conner et al, 2002;Pringsheim et al, 2015;Sorter et al, 2022).…”
Section: Methylphenidate and Emotional Regulationmentioning
confidence: 99%